Islamophobic Discourse of European Right-Wing Parties: A Narrative Policy Analysis - Oztig, Lacin Idil (SAGE PUBLICATIONS INC, 2023)
In Europe, in tandem with growing social anxiety regarding the so-called threat of Islamization, right-wing, populist parties have increasingly positioned themselves against Muslims and Islam to the point of becoming anti-Islam parties. This paper deconstructs Islamophobic discourses of the Freedom Party of Austria, the League, and the Alternative for Germany through narrative policy analysis and shows that they are built upon a similar narrative of a villain, victim, and hero. Muslims are depicted as villains that pose a threat to Europe, while national and European cultures are presented as victims, threatened by Islamic practices which are cast as irrational, dominant, and violence-prone. The depiction of Muslims as villains and European culture and society as victims gives these parties an opportunity to create a hero character for themselves. By presenting proposals, such as bans on Islamic practices, these parties narratively construct themselves as heroes determined to save their countries and European culture. Disregarding the heterogeneity of Muslims and Islamic traditions as well as the contribution of Muslim scientists and philosophers, these parties depict a simplistic picture of the world in which they appropriate for themselves the role of protector. Character construction in Islamophobic discourses raises important questions about multiculturalism, tolerance, and religious freedom in Europe.
Keywords: Islamophobia; right-wing populism; narrative policy analysis; the Freedom Party of Austria; the League; and Alternative for Germany; EXTREME-RIGHT; ISLAM; MOBILIZATION; POPULISM; ISSUE; CLASH; Sociology